Implementation of microbiological monitoring for predicting the multidrug-resistant phenotype of respiratory isolates based on risk factor analysis in patients with community-acquired pneumonia - O. P. Bobrova; S. K. Zyryanov; V. V. Chernaya; M. V. Statsenko; O. A. Parygina (Реальная клиническая практика: данные и доказательства)
Relevance. Studying risk factors for the presence of multidrug-resistant pathogens at the regional level, which predetermine multiple resistance, is an important component for personalizing the applied strategies of empirical antimicrobial therapy within the framework of epidemiological safety.   Objective. To study and analyze factors of polyresistance to optimize the choice of empirical antimicrobial therapy in patients with community-acquired pneumonia at the regional level.   Materials and methods. Clinical, microbiological and molecular genetic risk factors for the presence of multidrug-resistant pathogens of regional significance were retrospectively assessed in 533 patients with community-acquired pneumonia of inpatient profile. To predict the impact of risk factors on the multidrug resistance of respiratory isolates at the regional level, the method of constructing ROC curves was used.   Results. The leading respiratory isolates in the etiology of community-acquired pneumonia at the regional level were determined. A high level of associative resistance was demonstrated in respiratory isolates of Klebsiella pneumonia, Haemophylus influenzae, Escherichia coli, requiring mandatory microbiological and molecular genetic testing to select initial antimicrobial therapy. Frequency of carbapenemase production in the leading etiologically significant microorganism Klebsiella pneumonia was 60 %; the presence of multiple resistance mechanisms was 30 %, the presence of metallo-beta-lactamases of the NDM type was 42 %, respectively. In the constructed forecasting models, the following factors became practically significant for the implementation of polyresistance at the regional level: previous hospitalization and antimicrobial therapy, stay in long-term care facilities, prior treatment with carbapenem antibiotics, and associative production of carbapenemase with extended spectrum beta-lactamases.   Conclusion. The obtained results demonstrate the importance of a comprehensive analysis of clinical and microbiological factors for predicting the polyresistance phenotype in a specific medical organization and optimizing the empirical choice of antimicrobial drugs.